Ian McEwan's Enduring Love and postmodernity - Čechová, Kateřina (2006)
The thesis analyses Ian McEwans late novel Enduring Love in light of the theories of postmodernism. The aim is to suggest Enduring Loves debate over the change of the approach to science after the demise of modernity. Described is postmodernisms distrust of totality, and the main characters \x{201c}scientific\x{201d} mind is evaluated. The thesis also attends to the \x{201c}schizophrenia\x{201d} of Enduring Loves narration. The narrating charater Rose is identified as ambivalent, hence \x{201c}unreliable.\x{201d}